Źródła finansowania e-biznesu - Sobótka, Edyta (Funkcjonowanie e-biznesu. Zasoby, procesy, technologie, 2015)
Presented study is an attempt to indicate vide spectrum of sources of e-business founding, starting with more traditional ones like credits and loans, and ending with new method such as crowdfunding. Reader has the opportunity to learn about prospect created by European Union on years 2014–2020.This paper links different approaches from domain of law, finance and psychology. This document is also a glimpse on the current situation in Poland, which despite thoroughgoing characters is passing due to rapidly emerging new sources of founding e-business. The only permanent feature of e-bussines is permanent change.